HeartWare Ventricular Assist Device as Bridge to Transplant in Children and Adolescents. Issue 5 (3rd October 2013) - Padalino, Massimo A.; Bottio, Tomaso; Tarzia, Vincenzo; Bortolussi, Giacomo; Cerutti, Alessia; Vida, Vladimiro L.; Gerosa, Gino; Stellin, Giovanni
Abstract Limited options do exist for mechanical circulatory support as a bridge to transplantation in the pediatric population. This is especially true when it comes to intracorporeal technologies. We describe our successful experience with the use of HeartWare ventricular assist devices (HeartWare, Inc., Framingham, MA, USA) in three patients <16 years of age, as a successful and feasible bridge to transplant in patients weighing greater than 20 kg.